Ethnobotanical survey and research on bsang plants in Xizang Autonomous Region - ZHANG Xiong1,2, FENG Haowen1,3, WANG Jin1,3, LIN Lei1,3, WANG Yuhua1* (Guangxi Zhiwu)
Bsang is a folk activity with unique ethnic cultural characteristics on the Qinghai-Tibet Plateau(QTP), and plays an important role in the daily life of Zang people. There are abundant bsang plant resources and related bsang cultural knowledge on the QTP, to investigate, document, and study Xizang bsang plants and related traditional knowledge, the research team conducted four ethnobotanical surveys on bsang plants in Xizang Autonomous Region, China. Interviews were conducted with 459 informants from 23 townships, documenting 83 species of bsang plants belonging to 36 genera across 19 families. The results are as follows:(1)People of different regions, ages, and genders possess extensive knowledge of bsang plants.(2)Hordeum vulgare var. coeleste, Juniperus indica, and Rhododendron anthopogon have high cultural value index(CV), making them crucial in bsang activities.(3)The utilization of bsang plants demonstrates regional and substitutive characteristics, reflecting the local practices of scientifically managing and sustainably collecting of bsang plant resources. This study contributes to the inheritance of bsang activities and the biodiversity conservation and sustainable utilization of bsang plant resources.